A Two-Step Lyssavirus Real-Time Polymerase Chain Reaction Using Degenerate Primers with Superior Sensitivity to the Fluorescent Antigen Test. (15th April 2014) - Suin, Vanessa; Nazé, Florence; Francart, Aurélie; Lamoral, Sophie; De Craeye, Stéphane; Kalai, Michael; Van Gucht, Steven
Abstract : A generic two-step lyssavirus real-time reverse transcriptase polymerase chain reaction (qRT-PCR), based on a nested PCR strategy, was validated for the detection of different lyssavirus species. Primers with 17 to 30% of degenerate bases were used in both consecutive steps. The assay could accurately detect RABV, LBV, MOKV, DUVV, EBLV-1, EBLV-2, and ABLV. In silico sequence alignment showed a functional match with the remaining lyssavirus species. The diagnostic specificity was 100% and the sensitivity proved to be superior to that of the fluorescent antigen test. The limit of detection was ≤1 50% tissue culture infectious dose. The related vesicular stomatitis virus was not recognized, confirming the selectivity for lyssaviruses. The assay was applied to follow the evolution of rabies virus infection in the brain of mice from 0 to 10 days after intranasal inoculation. The obtained RNA curve corresponded well with the curves obtained by a one-step monospecific RABV-qRT-PCR, the fluorescent antigen test, and virus titration. Despite the presence of degenerate bases, the assay proved to be highly sensitive, specific, and reproducible.